THE DEVELOPMENT OF MOODLE BASED ENGLISH READING MATERIAL (A case at Multimedia Department Student to Year Tenth of Telekomunikasi Tunas Harapan Vocational High School Semarang) - Nurhayati, Dyah (Faculty of Languages Ã¢â¬â¹Ã¢â¬â¹and Arts, State University of Semarang, 2013)
This study was a research and development (R&D), which aimed at developing types of reading materials for the tenth year multimedia students of SMK Telekomunikasi Tunas Harapan, finding out the contents validity of the developed material; the quality of the developed material and, whether or not the developed material could improve the reading comprehension of the students. The result of this study shows that: The existing syllabus and material did not cover their needs since the syllabus and the material were designed to be used for all departments , based on the expert validation, it was confirmed that the developed material had a very high validity; from the result of the expert judgment based on the criteria of good ESP material and good e- learning material, the developed material was categorized into very good material; and the result of the field study shows that the developed material could improve the studentsâ reading comprehension. The studentsâ mean score for those tests, which reflect the studentsâ reading comprehension, increased from 40.9 in pre-test, to 66.3 in post- test I, and 79.1 in post-test II. Based on the result of the questionnaire, the students had strongly positive attitude toward the developed material.